Guarding the invisible dragons - West, Tracey, 1965-; Loveridge, Matt (New York, NY : Scholastic, Inc., 2022)
A nest of invisible baby dragons has been discovered in Queen Sofia's castle so Drake, Worm, and Val, Carlos's cousin, must journey to the dangerous Dove Island to find the parents and the fruit that keeps the dragons' invisible powers.
3.2
K-3
560L
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Adventure stories; Dragons -- Fiction; Magic -- Fiction; Fantasy; Adventure and adventurers -- Fiction; Fantasy fiction; Action and adventure fiction